A novel personalized homogenous finite element model to predict the pull-out strength of cancellous bone screws - Alireza Rouyin; Mohammadjavad (Matin) Einafshar; Navid Arjmand (Journal of Orthopaedic Surgery and Research)
Abstract Background Orthopedic surgeries often involve the insertion of bone screws for various fixation systems. The risk of postoperative screw loosening is usually assessed through experimental or finite element (FE) evaluations of the screw pull-out strength. FE simulations are based on either personalized complex but accurate heterogeneous modeling or non-personalized simple but relatively less accurate homogeneous modeling. This study aimed to develop and validate a novel personalized computed tomography (CT)-based homogeneous FE simulation approach to predict the pull-out force of cancellous bone screws. Methods Twenty FE simulations of L1-L5 vertebral screw pull-out tests were conducted, i.e., 10 heterogeneous and 10 homogenous models. Screws were inserted into the lower-middle region of vertebrae. In our novel homogeneous model, the region around approximately twice the diameter of the screw was used as a bone material reference volume. Subsequently, the overall material property of this region was homogeneously attributed to the entire vertebra, and pull-out simulations were conducted. Results The mean error of the predicted pull-out forces by our novel homogenous simulations was ~ 7.9% with respect to our heterogeneous model. When solely the cancellous bone was involved during the pull-out process (i.e., for L1, L2, and L3 vertebral bodies whose cortical bone in the inferior region is thin), the novel homogenous model yielded small mean error of < 6.0%. This error, however, increased to ~ 11% when the screw got involved to the cortical bone (for L4 and L5 vertebrae whose cortical bone in the inferior region is thick). Conclusion The proposed personalized CT-based homogenous model was highly accurate in estimating the pull-out force especially when only the cancellous bone was involved with the screw.